Repenser la fiction dans ses rapports au numérique - Marc Marti (Cahiers de Narratologie)
The aim of the conference was to examine several categories at once in order to rethink the evaluation of fiction, particularly in contemporary creations. We return to some of the key points in order to propose a postface that outlines several possible directions, looking in particular at the relationship between creation and reception of digital material, which must undoubtedly be seen as the keystone of the emergence of new practices, those of 'digital cultures'. We will first attempt to define the notion of aesthetic categories, starting with a retrospective look at the classical era and the emergence and use of the concept of fiction. We will then assess the transformation that digital technology has brought to fiction. We will need to identify both the material and the new methods of production and distribution that it has engendered, but also to consider what its potential is and how it has been used in the creation of fiction.